FINTECH SYARIAH DALAM MANAJEMEN KEUANGAN MIKRO: TINJAUAN KONSEPTUAL TERHADAP INKLUSI KEUANGAN DIGITAL - Dina Lutfiatunnisa, Farah; Septiani Putri, Adelia; Addini Magfiroh, Sabrina; Avrilia, Diva; Nuraulia, Maya; Rahman, Rahman (At-Tawazun, Jurnal Ekonomi Syariah, 2025)
Advances in digital technology have transformed financial management practices, including those within Islamic finance. This study examines the role of sharia-compliant financial technology (fintech) in strengthening microfinance management and enhancing digital financial inclusion in Indonesia. Using a qualitative approach supported by a conceptual review, the study highlights the connection between Islamic ethical values and technological innovations implemented in Islamic microfinance institutions (MFIs). Sharia fintech not only facilitates financial transactions but also serves as an instrument for promoting an ethical, transparent, and equitable financial system aligned with sharia principles. The findings indicate that integrating sharia fintech with MFIs can broaden access to financial services, particularly for underserved communities and micro-entrepreneurs who often encounter barriers to formal financing. Despite these benefits, several challenges remain, such as regulatory gaps, limited digital literacy, and concerns over data security. Therefore, strong collaboration between the government, financial institutions, and technology sector stakeholders is essential to ensure that sharia fintech grows sustainably and delivers meaningful social and economic benefits to society.